Development of Performance Assessment Instrument to Measure Students Laboratory Skills in Thermochemistry Practicum Exothermic and Endothermic Reactions - Oktavilani, Nabila Defti; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This development research was conducted to produce a performance assessment instrument that is feasible to use to measure students' laboratory skills in thermochemical practicum activities for exotherm and endotherm reactions based on field investigations and literature reviews that have been completed. The feasibility of performance assessment instruments is reviewed on validity, reliability, and practicality. The type of research used is research and development (Research and Development) with the 4-D method. The validity data was obtained using a validation questionnaire from the validator's assessment. Reliability data was obtained from student laboratory skills scores from two assessors. Affectivity data is obtained from the educator response questionnaire filled out by educators after using the performance assessment instrument. The validity results showed that the aspects of the content component of the performance assessment instrument were declared valid, the presentation feasibility aspect was declared valid, the physical criteria aspect was declared valid, the illustration aspect was declared valid, and the language aspect was declared valid. Reliability results based on the inter-rater reliability analysis obtained a kappa coefficient 0.739 with excellent agreement. Practicality results based on educator responses that received a percentage of 100% with very good criteria. Based on the results of the performance assessment instrument's validity, reliability, and practicality, it is declared feasible to use it to measure the science process skills of students in the laboratory.